New-onset systemic sclerosis and scleroderma renal crisis under docetaxel. Issue 3 (October 2021) - Debien, Véronique; Petitdemange, Arthur; Bazin, Dorothée; Ederle, Carole; Nespola, Benoit; Merdji, Hamid; Olagne, Jérome; Martin, Thierry; Guffroy, Aurélien; Pflumio, Carole
Systemic sclerosis is a rare systemic autoimmune disease characterized by microvascular impairment and fibrosis of the skin and other organs with poor outcomes. Toxic causes may be involved. We reported the case of a 59-year-old woman who developed an acute systemic sclerosis after two doses of adjuvant chemotherapy by docetaxel and cyclophosphamide for a localized hormone receptor + human epithelial receptor 2—breast cancer. Docetaxel is a major chemotherapy drug used in the treatment of breast, lung, and prostate cancers, among others. Scleroderma-like skin-induced changes (morphea) have been already described for taxanes. Here, we report for the first time a case of severe lung and kidney flare with thrombotic microangiopathy after steroids for acute interstitial lung disease probably induced by anti-RNA polymerase III + systemic sclerosis after docetaxel.